2022
DOI: 10.3390/molecules28010083
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Metabolism in Tetrastigma hemsleyanum Diels et Gilg Based on Metabolome Analysis and Transcriptome Sequencing

Abstract: Tetrastigma hemsleyanum Diels et Gilg, known as a “plant antibiotic”, possesses several attractive properties including anti-inflammatory, anti-tumor, and antioxidant effects, with its efficacy being attributed to flavonoids. However, the flavonoid biosynthesis of T. hemsleyanum has rarely been studied. In this study, we investigated the flavonoid metabolism of T. hemsleyanum through metabolome analysis and transcriptome sequencing. The metabolomic results showed differences in the flavonoids of the leaves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Through correlation network analysis, most of the metabolites were correlated with PER1 . Bai et al [ 23 ] previously investigated flavonoid metabolism in the roots and leaves of three-year-old SYQ. The results showed that CHI and UFGT were potential key genes involved in the biosynthesis of most flavonoids in SYQ.…”
Section: Discussionmentioning
confidence: 99%
“…Through correlation network analysis, most of the metabolites were correlated with PER1 . Bai et al [ 23 ] previously investigated flavonoid metabolism in the roots and leaves of three-year-old SYQ. The results showed that CHI and UFGT were potential key genes involved in the biosynthesis of most flavonoids in SYQ.…”
Section: Discussionmentioning
confidence: 99%